2018
DOI: 10.1021/acssuschemeng.8b03262
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Structural Properties of Lignin–Carbohydrate Complexes in Bamboo Residues and Its Functionality as Antioxidants and Immunostimulants

Abstract: Lignin–carbohydrate complexes (LCCs), a significant component of plant cell walls, have been found to bear biological functionality as antioxidants in food and as immunostimulants for living cell. In this work, a lignin-rich and a carbohydrate-rich LCCs preparations were isolated from bamboo residues (bamboo green and bamboo yellow). Each preparation was characterized by chemical composition and LCCs linkage types and quantities by high performance anion exchange chromatography (HPAEC) and NMR technologies (qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 35 publications
6
61
0
Order By: Relevance
“…For quantification of LILs and LCLs, the aromatic regions (105-160 ppm) of all spectra were integrated and normalised to 600 resulting that the integral values of the other regions were expressed per 100 aromatic rings. Those integrals were used to convert the relative signals elucidated by 2D-HSQC into 13 C based number per aromatic rings (n°/100ar) as previously reported in the literature. 4,6,17,34 Calculations were done using the following equations (1) and (2):…”
Section: Results Andmentioning
confidence: 99%
See 2 more Smart Citations
“…For quantification of LILs and LCLs, the aromatic regions (105-160 ppm) of all spectra were integrated and normalised to 600 resulting that the integral values of the other regions were expressed per 100 aromatic rings. Those integrals were used to convert the relative signals elucidated by 2D-HSQC into 13 C based number per aromatic rings (n°/100ar) as previously reported in the literature. 4,6,17,34 Calculations were done using the following equations (1) and (2):…”
Section: Results Andmentioning
confidence: 99%
“…8,9 Their biological properties were as well described in various papers including their antioxidants and anti-UV efficacies for cosmetic development and their pharmacological activities for human medicine. [10][11][12][13] For industrial purposes, it has been demonstrated that LCCs could be recovered from various residual feedstocks of lignocellucosic biomass. Narron et al deciphered their presence in the hydrolyzates resulting from the autohydrolysis pretreatment of hardwood and nonwood biomasses.…”
Section: Introduction Lignin Carbohydrate Complexes (Lccs) Have Beenmentioning
confidence: 99%
See 1 more Smart Citation
“…112 Studies have shown that LCCs may be involved in the induction of anti-tumor, anti-microbial, anti-HIV and antioxidation activity. 112,114,115 Polysaccharide portions of LCCs are composed of various types of sugars, such as glucose, arabinose, mannose, galactose, fucose and xylan. 114 LCCs from bald cypress, birch and rice straw show an extremely broad molecular weight distribution from 1.5 to 85 kDa.…”
Section: Anti-tumor Activity Of Gut Microbiotamentioning
confidence: 99%
“…They studied how to inhibit the production of PCFs, but not how to utilize them. There are few studies on the microstructure and mechanical properties of PCFs.In recent years, microscopic imaging and spectral characterization methods have been used in nanostructure and chemical composition analyses of cell walls of plant fibers like wood fibers [11][12][13][14][15][16], bamboo fibers [17][18][19][20][21][22], and cotton fibers [23,24]. Chen et al [25] characterized the aggregation of microfibrils in the cross-section of thin-wall cells using the atomic force microscopy (AFM) technique.…”
mentioning
confidence: 99%